Uridine alleviates the aging of alveolar epithelial cells in idiopathic pulmonary fibrosis through the Keap1-Nrf2 signaling pathway - Chenchun Ding; Renjie Zuo; Quan Liao; Zhenzhen Guo; Junjie He; Ziwei Ye; Guoyan Liu (Scientific Reports)
Abstract Idiopathic pulmonary fibrosis (IPF) is an age-related disease with an unclear pathogenesis. The senescence and insufficient regeneration of alveolar epithelial cells are significant factors in the development and progression of IPF. Currently, effective treatment methods are lacking. The aim of this study is to explore the mechanism of action of uridine in delaying the aging of AECs and intervening in IPF. In vitro, Western blot and qRT-PCR analyzed uridine’s effects on bleomycin-induced senescence, EMT, cell viability, and cell cycle. In vivo, uridine’s impact on lung aging and fibrosis in BLM-induced mice was assessed by weight, staining, Ashcroft scoring, and Western blot. Uridine reduced senescence markers in A549 cells, suppressed epithelial-mesenchymal transition, improved antioxidant capacity, and delayed pulmonary fibrosis and lung aging in mice. The effects of uridine were mediated through the NRF2 signaling pathway, which regulates antioxidant defense and autophagy. Uridine enhanced autophagic degradation of Keap1, possibly through p62/SQSTM1-mediated autophagy. These findings suggest that uridine inhibits AEC senescence via the NRF2 pathway, mitigating IPF progression and offering a potential strategy for treating age-related pulmonary fibrosis by targeting oxidative stress.